New venture creation: a systematic review of associated literature - Donaldson, Colin (2020)
New venture creation is an integral facet of entrepreneurship and as consequence has been subject to increased research attention within extant literature. Although momentum has been gained in search of explicating this broad and diverse phenomenon there is still great potential to further our understanding. Progress in expanding knowledge will be most effective if we are able to constructively build upon explicitly recognised common foci that can serve as a foundation to cooperative contribution. The current article has the objective of providing an up-to-date thematic overview via systematic means of the main research interests that are being attended to within the new venture creation domain. The study is based on a comprehensive search of the SCOPUS database up until, and including, the year 2017. Thus, there is the useful and original provision of a parsimonious overview of the many heterogenous factors implicated within the process. Citation analysis is used as a framework to distinguish influential publications and their interconnections, with intellectual foundations and theoretical underpinnings driving research presented. A key implication of the work is the provision of a classification of key trending themes based on four priority constructs that can inspire new research avenues and greater collaboration in future investigative efforts.